PENGARUH PANGSA PASAR, RASIO LEVERAGE DAN RASIO INTENSITAS MODAL TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG GO-PUBLIC DI INDONESIA - Umi Murtini; Dwi Setia Anggraeni (Jurnal Riset Akuntansi dan Keuangan, 2006)
This study aims examining influence of ,market share, leverage ratio, capital intensity to profitability in manufactur sector in Indonesia. The Study uses /inancial report from manufactur sector especially in food and baverage, from 1999 until 2003 for 20 tirms. Results of this study are: first, Debt Total Asset @M) and capital intensity enfluence si4ntrtcantly Return on Assets, meanwhile market share and and Debt equty ratio do not influence to Return on Assets. Second, Debt total assets, Debt equity ratio, and capital intensity intluence significantly Return on Equity, meanwhile market share do not influence to return on equity.Keywords: ROA, ROE, Pangsa Pasa7 Leverage Ratio, Capital Intensity Rasio.